Mangrove forest: degradation and rehabilitation - Abd Rahman, Mazni Adibah; Asmawi, M. Zainora (2014)

(untitled)
Mangroves are highly beneficial as they have many environmental and social functions. They yield many valuable products, while also performing, free-of-cost, many important functions that support the often dense coastal populations. Economically, they are thus highly important, be it at local, regional, national or even international level. Mangroves existence and values are always taken for granted and unrecognized over the years, thus resulting on its disappearance in many parts of the globe. These impacts are likely to continue and worsen day by day, as the human population overtook mangrove population. In some areas, the health and productivity of the forests have declined significantly. Therefore, the nature of this research paper is to study the contextual settings of mangroves environment largely based on secondary data. The mangrove depletion is a tragic loss that differs from habitat to habitat but is generally tied directly or indirectly to human activities. Besides man-made pressures, the mangroves are degraded by environmental stress factors. In a larger scale, over fishing, loss of mangrove and sea grass habitats are considered to be major causes for the serious declination in number of marine mammals such as Manatees and Dugongs. The negative environmental and socioeconomic impacts on mangrove ecosystems have led many government and non-government agencies, together with civil societies, to launch mangrove conservation and rehabilitation programmes. To conclude this paper, the society needs to regard the importance of mangrove to safeguard the Mother Nature in line with the aspiration of sustainable development.